Dynamic Query Forms for Non-Relational Database Queries (International Journal of Engineering and Computer Science, 2014)
Modern scientific databases and web databases maintain large and heterogeneous data. These real-world databasescontain over hundreds or even thousands of relations and attributes. Traditional predefined query forms are not able to satisfyvarious ad-hoc queries from users on those databases. This paper proposes DQF, a novel database query form interface, which isable to dynamically generate query forms. The essence of DQF is to capture a user’s preference and rank query form components,assisting him/her to make decisions. The generation of a query form is an iterative process and is guided by the user. Ateach iteration, the system automatically generates ranking lists of form components and the user then adds the desired formcomponents into the query form. The ranking of form components is based on the captured user preference. A user can alsofill the query form and submit queries to view the query result at each iteration. In this way, a query form could be dynamicallyrefined till the user satisfies with the query results. We utilize the expected F-measure for measuring the goodness of a queryform. A probabilistic model is developed for estimating the goodness of a query form in DQF. Our experimental evaluation anduser study demonstrate the effectiveness and efficiency of the system.